Predicting the invasiveness of pulmonary adenocarcinoma using intratumoral and peritumoral radiomics features - Hong, Jingjing; Yang, Liyang; Huo, Jiekun; Huang, Guoci; Shan, Bowen; Cai, Tingting; Zhang, Lianlian; Huang, Weikang; Wen, Ge (Frontiers in Medicine, 2025)
ObjectiveTo evaluate the predictive value of CT radiomics features within and surrounding tumors in determining the invasiveness of primary solitary nodular pulmonary adenocarcinoma.MethodsThis retrospective study analyzed 107 patients with pathologically confirmed nodular pulmonary adenocarcinoma who underwent conventional non-enhanced CT Scans in our hospital from 2019 to 2023. Patients were categorized as non-invasive or invasive based on pathology findings. Clinical and imaging data from both groups were collected and compared, and logistic regression was used to independent factors associated with invasiveness. Radiologists manually outlined 3-dimensional regions of intratumoral and peritumoral areas to extract radiomics features, creating separate intratumor, peritumor, and combined intra-peritumor radiomics models. Radiomics models were trained using LASSO with 10-fold cross-validation in training dataset. Additionally, integrated models combining radiomics with clinical data were developed: intratumor-clinical, peritumor-clinical, and an intra-peri-clinical models.ResultsOf the 107 patients, 73 were in the non-invasive group (mean age 49.73 ± 13.92, 22 males) and 34 were in the invasive group (mean age 57.53 ± 12, 14 males). The clinical model identified average nodule diameter and vascular type as independent risk factors for invasiveness (both p < 0.025). The combined intra-peri-clinical model demonstrated superior predictive performance compared to other models, with an AUC of 0.93, sensitivity of 0.91, and specificity of 0.86.ConclusionThe combined model incorporating intratumor and peritumor radiomics features with clinical data showed significant value in predicting the invasiveness of nodular pulmonary adenocarcinoma, aiding in the precise selection of surgical methods.